(untitled) (Modern education and development, 2025)
Relevance. According to the World Health Organization, approximately 200 million people worldwide are infected with giardiasis annually, of which 500 thousand (0.25%) develop clinical manifestations. In Russia, up to 150 thousand cases are registered annually, 80% of which occur in children under 14 years of age. In particular, this indicator is increasing significantly in Uzbekistan.